Wartości a wartości polityczne w kształtowaniu bezpieczeństwa społecznego - Plecka, Danuta (Political Preferences, 2013)
Social security has become in recent years an important element in the discourse about the quality of life on individualism and social group. Can not be successful introduction of social security without development elements, even in the from of human capital. This however has a poor design possibilities, if the public is desprived of the Community dimension of security, which is an integral part of social capital.